(untitled) (Bangladesh Journal of Medical Science, 2023)
Introduction: Inflammation of the supporting tissues which is also known as periodontitis contributes to the major etiological factor for tooth loss. Consortium of pathogenic bacteria with elevated levels lead to onset and progression of periodontal disease. Gram negative bacteria, primarily severe anaerobes, are responsible for most of it. Aims and Objectives: The present study aimed to assess the presence of Treponema denticola in periodontal disease in different subgingival plaque samples collected from the oral cavity of 30 patients diagnosed with chronic periodontitis. The plaque samples were compared with similar plaque samples of 15 healthy patients. Method: Subgingival dental plaque samples from shallow and deep crevices were examined for the presence of bacterial DNA using the PCR method, which enables the simultaneous identification of multiple bacterial genomes. Results: PCR results show amplification and quantification of T. denticola in 10 out of 15 patients in group-1, 9 out of 15 patients in group-2, and 4 out of 15 patients in group-3. The statistical analyses of the results show that they are statistically significant. Conclusion: According to the aforementioned study, PCR microorganism identification is sensitive and specific. For early infection diagnosis and subsequently for the prevention and treatment of periodontal disease, a rapid and accurate assessment of periodonto-pathogens is crucial. Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.93-99